Penerapan Manajemen Kesehatan Panti Benih Udang Di Kalianda Lampung Selatan - Rico Wahyu Prabowo; Sri Waluyo; Yudha Trinoegraha Adiputra; Rara Diantari; Esti Harpeni (Jurusan Perikanan dan Kelautan, 2015)
Shrimp culture drives the national economy that are included in the program of industrialization of fisheries in the economic development programs of blue ( blue economy ). Shrimp farming in Lampung province remains a mainstay of the region as a foreign exchange earner . Kalianda , South Lampung is the center hatchery tiger shrimp (Penaeus monodon) and vannamei shrimp (Litopeneaeus vannamei ) the largest in Lampung. research conducted to observe the shrimp health management applied by growers of black tiger shrimp and vannamei shrimp in South Lampung and learn relationship between seed health management with quality seeds and tiger prawn shrimp vannamei shrimp health management dihasilkan. Data obtained by interview and the quality of shrimp seed obtained from observations in the laboratory with the observed light response, swimming activity, abnormality, gut contents, lipid droplets, the condition of the hepatopancreas and pigmentation. There are 22 hatchery were observed with the application of the value of health management in the high category for the third hatchery , hatchery medium category 6 and category bneih low at 13 homes. The quality of virus-free shrimp WSSV and IHHNV and the amount of bacteria in the body are normal and healthy shrimp was observed in the overall nursing bneih diamati. Relation between hatchery management application health and seed quality is reflected by the equation Y = 0,019X2 - 1,358X + 52.49 with the coefficient of determination ( R2 ) of 0.419. This relationship indicates that the quality of shrimp seed is determined by the health of hatchery management practices (r = 0.647). This study reinforces the importance of implementing health management hatchery known by farmers with biosecurity as a form of sustainable shrimp farming .